Opening of the northwest passage : the impact and possibilities - Sim, Chee Leong. (2012)
Rising world temperature has made the Northwest Passage (NWP) become ice free for the first time in year 2007. This phenomenon has started to draw the attention of many shipping circles as the NWP offers a significant distance saving between the east and the west as compared to the current Panama Canal and Suez Canal route. In this paper, the competitiveness of the NWP was determined in Work Package 3 (WP3). In order to determine its competitiveness in terms of safety, congestion, physical restriction, service availability and accessibility against the two canals, survey questionnaires were distributed out to 150 shipping companies in Singapore. Survey response were then analysed with Pugh Matrix Analysis and three weighted score were calculated for each of the sea routes. After that, the competitiveness of the NWP against the Panama Canal and the Suez Canal were determined by comparing the weighted scores. In Work Package 4 (WP4), the economic feasibility of container shipping via the NWP was evaluated. Although a lot of similar researches were done previously, there is still a lack of research investigating the relationship between new-building price of an arctic-classed containership and different navigable seasons in the NWP as well as their impact on overall shipping cost for ships sailing through the NWP. To investigate this relationship, ten 5,100 arctic-classed containership prices were used, each having an extra 10-100% new-building premium than a conventional 5,100 blue-water class containership. Besides that, three navigable seasons in the NWP were employed, which respectively have 60, 120, 180 days available for transit. With all these parameters mentioned above, this resulted in 31 different scenarios (30 scenarios for the NWP and one scenario for conventional sea route). As comparisons were made between the NWP against the Panama Canal and Suez Canal, ultimately 62 annual total cost per TEU transported per year were calculated. Results in WP3 shows that the NWP is not an alternative of the Panama Canal and the Suez Canal for the time being, whereas results in WP4 shows that the NWP is not economical feasible in the near future (in 10 years’ time) but economic possible in the future, as further thinning of ice reduces total shipping cost and at the same time increases revenue.